THE EFFECT OF DIGITAL FINANCIAL, CREDIT RISK, OVERHEAD COST, AND NON-INTEREST INCOME ON BANK STABILITY - Wiwi Idawati; Shania Anasthasia Syafputri (FEB-UP Press, 2022)
ABSTRACT This research aims to find out and analyze the influence of digital finance, credit risk, overhead cost, and non-interest income on the stability of banks from the banking industry included in conventional banks listed on the Indonesia Stock Exchange (IDX) in the period 2016 to 2020. Sample selection uses the purposive sampling method. The number of samples used in this study amounted to 40 Conventional Banks registered IDX. The independent variable consists of Digital Finance measured using dummy variables, namely 1 if the bank launches a mobile banking application and 0 if vice versa, Credit Risk measured using Non Performing Loan (NPL), Overhead Cost measured using overhead expense ratio divided by total assets, and Non-Interest Income as measured by non-interest income ratio divided by total operating income. Furthermore, the study's dependent variable is Bank Stability as measured using Z-scores. This study compares two research results based on the COVID-19 Pandemic period, namely research I before COVID-19 with 2016 to 2019 and research II when COVID19 with only 2020. The results showed that Digital Finance had a positive effect on both studies, Credit Risk had a negative effect on both studies, Overhead Cost had no effect, and Non-Interest Income had no effect on the study period I and negatively on the study period II. Keywords: Digital Finance, Mobile Banking, Credit Risk, NPL, Overhead Cost, Non-Interest Income